Perceptions of eHealth and digitalization among professional anaesthesia personnel : A Swedish national study - Jildenstål, Pether; Viseu, Camilla; Hermander, Kristian; Sjöberg, Carina; Hallén, Katarina; Schnorbus, Randolph; Augustinsson, Annelie (Acta Anaesthesiologica Scandinavica, 2025)
BACKGROUND: The objective of this study was to evaluate anaesthesia care professionals' perceptions and attitudes regarding the implementation and advancement of digital solutions in perioperative care. METHODS: Anaesthesia personnel working in public Swedish institutions where anaesthesia is administered were invited to respond to an online survey regarding their attitudes towards digitalization in the workplace and their perceptions of information provision and future digitalization within anaesthesia and surgical healthcare. Data were analyzed using descriptive statistics, independent-samples Kruskal-Wallis tests, and post-hoc pairwise comparisons. RESULTS: The survey response rate was 64.0% (n = 627). Most respondents agreed/strongly agreed that digital solutions facilitate their work, the preoperative preparation, patient participation, and being involved in the patients' journeys throughout the perioperative care process. The majority also agreed/strongly agreed that digital solutions could make more patients adequately prepared before anaesthesia/surgery, reduce the number of non-optimized patients, and adapt the perioperative process to the patients' individual needs, as well as lead to reduced costs for the healthcare provider and reduced cancelled anaesthesia/surgeries. However, there were statistically significant differences between responses in relation to age groups, where the largest differences were observed between respondents in the age groups 20-30 and 61-70 years and in relation to what part of Sweden respondents worked in, with the largest differences between respondents working in Southern Sweden and the middle part of Sweden. CONCLUSION: Swedish anaesthesia personnel are confident that digital solutions may enhance the efficiency of care within the anaesthesia setting. However, varying perceptions on the benefits and necessity of digital solutions are indicated.
Keywords: Humans; Sweden; Middle Aged; Adult; Male; Female; Aged; Attitude of Health Personnel; Telemedicine; Young Adult; Surveys and Questionnaires; Perception; Anesthesiologists; Anesthesiology